Total flavonoids from Ampelopsis megalophylla suppress proliferation of vascular smooth muscle cells in vivo and in vitro - Zhenpeng Qiu; Junxuan Zhou; Junjie Hu; Yong Wu; Guohua Zheng (Universidade de São Paulo, 2018)
ABSTRACT Various benefits of flavonoids for ameliorating cardiovascular diseases have been demonstrated. However, the lowering effects on blood pressure caused by antiproliferative potentials of flavonoids in vascular smooth muscle cells are rare. In this study, the antihypertensive effects of total flavonoids from Ampelopsis megalophylla were investigated. The dynamic pressure values and the rate of media thickness versus lumen diameter were measured by the tail-cuff system and H&E staining in vivo, respectively. The mRNA expressions of ACE, Ang II, eNOS, c-Myc, cyclin D1 and p27Kip1 in thoracic aorta or A7r5 cells were measured by qPCR, respectively. The protein expressions of c-Myc, Cyclin D1, p27Kip1 and β-catenin in tissues or A7r5 cells were measured by Western blot assay. Total flavonoids of A. megalophylla (TFAM) reduced the expressions of ACE and Ang II, and elevated the content of eNOS in thoracic aorta cells of SHRs. Furthermore, TFAM decreased the mRNA and protein expressions of c-Myc and cyclin D1 by repressing the Wnt/β-catenin-mediated TCF/LEF transcriptional activation both in vivo and in vitro, which is synergetic with the up-regulation of p27Kip1 expression. Our study provided evidence for developing flavonoids from A. megalophylla as herbal supplements to prevent against cardiovascular diseases by suppressing vascular remodeling.